2011
DOI: 10.4103/0255-0857.81793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enzyme immunoassays detecting Helicobacter pylori specific IgG in serum and saliva with endoscopic and biopsy findings in patients with dyspepsia

Abstract: Due to their high sensitivity and specificity in diagnosing HP-associated DU and gastritis, serum and saliva antibody testing seems to offer a valuable alternative to invasive procedures especially in areas of high HP prevalence such as ours; saliva antibody testing is simple and practical especially in children and in difficult patients who resent venipuncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…During a survey, the sensitivity and specificity of salivary antibody for detection of H. pylori were 80.9% and 95.3% respectively, that the specificity was significantly higher than ours ( 24 ). El-Mekki et al found no significant difference between serum and salivary antibody levels regarding endoscopic findings, which was concordant with our study ( 23 ). In this research, serum and salivary antibodies for diagnosis of H. pylori were acceptable with no statistical difference, while El-Fakhfakh et al found that the salivary antibodies were more sensitive and specific than serum antibodies ( 5 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During a survey, the sensitivity and specificity of salivary antibody for detection of H. pylori were 80.9% and 95.3% respectively, that the specificity was significantly higher than ours ( 24 ). El-Mekki et al found no significant difference between serum and salivary antibody levels regarding endoscopic findings, which was concordant with our study ( 23 ). In this research, serum and salivary antibodies for diagnosis of H. pylori were acceptable with no statistical difference, while El-Fakhfakh et al found that the salivary antibodies were more sensitive and specific than serum antibodies ( 5 ).…”
Section: Discussionsupporting
confidence: 93%
“…Rahman et al reported sensitivity and specificity of serum IgG against H. pylori about 96.7% and 42.8% respectively, that the sensitivity was more than our findings and the specificity was lesser than our results ( 22 ). In current work, the salivary IgG revealed a sensitivity and specificity of 85% and 82% but El-Mekki et al indicated a high sensitivity (95%) and low specificity (70%) of ELISA test ( 23 ). In a survey of Krishnaswamy et al, sensitivity (79.31%) of salivary IgG was acceptable, but specificity (63.64%) was low ( 1 ).…”
Section: Discussioncontrasting
confidence: 55%
“…7 - 8 Saliva H. pylori antibody testing and stool antigen testing can readily be manipulated, as many studies have reported. 9 , 10 However, it was seldom reported regarding saliva H. pylori antigen testing. 11 H. pylori Saliva Test Cassette (HPS) is to use monoclonal antibody to specifically identify urease in saliva after H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%